Boosting uniform charge distribution using 3D rigid electrodes with interconnected gyroid channels to achieve stable and reliable zinc-ion batteries. Issue 13 (28th February 2022) - Zhang, Minggang; Hu, Taotao; Wang, Xiao; Chang, Peng; Jin, Zhipeng; Pan, Longkai; Mei, Hui; Cheng, Laifei; Zhang, Litong
Abstract : 3D gyroid electrodes with excellent connectivity and rigidity boost uniform charge distribution within the 3D structure, achieving stable and reliable zinc ion batteries. Abstract : Zinc ion batteries (ZIBs) are regarded as competitive candidates for next-generation energy storage systems because of their low cost, environmental friendliness, and high safety. Nevertheless, unsatisfactory long-term stability and inadequate environmental adaptability resulting from the Zn dendrite and unstable electrode architecture hinder their further development. Here, a 3D rigid electrode with a gyroid architecture is reported. The rigid electrode with 3D connecting pores ensures the uniformity of ion deposition and the adequacy of electrochemical reactions by balancing the ion and electron distribution. Thus, a pouch aqueous ZIB based on the rigid 3D electrode shows an excellent energy density of 33.3 mW h cm −3 at 6.8 mW cm −3 . Furthermore, the organized channels and stable rigidity of the gyroid architecture provide an opportunity to achieve ZIBs with ultra-high stability and safety. A solid-state ZIB built with the rigid 3D electrode and in situ polymerized conformal solid-state electrolyte exhibits satisfactory long-term cycle stability (capacity retention of 88.75% after 500 cycles) with outstanding coulombic efficiency (∼100%). More importantly, the final device performs well under natural and harsh conditions, such as soaking, high and low temperature, compression, and mechanical impact, opening a new horizon for future design and manufacture of high-reliability ZIBs with high environmental adaptability.